1978
DOI: 10.1073/pnas.75.12.5874
|View full text |Cite
|
Sign up to set email alerts
|

Specific RNA sequences and gene products of MC29 avian acute leukemia virus

Abstract: The 28S RNA of the defective avian acute leukemia virus MC29 contains two sets of sequences: 60% are hybridized by DNA complementary to other avian tumor virus RNAs (group-specific cDNA) and 40% are hybridized only by MC29-specific cDNA. Specific and group-specific sequences of viral RNA, defined in terms of their large RNase TI-resistant oligonucleotides, were located on a map of all large T, oligonucleotides of viral RNA. Oligonucleotides representing MC2-specific sequences of viral RNAmnapped between 0.4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
123
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 32 publications
13
123
0
Order By: Relevance
“…This sequence maps between 2.5 and 4 kb from the 3' end of MC29 RNA and codes together with other sequences of viral RNA for a MC29-specific, nonstructural protein of 120,000 daltons (9) that is also expressed in transformed cells (4). Therefore, it was suggested that this sequence is a candidate for the onc gene of MC29 (9).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This sequence maps between 2.5 and 4 kb from the 3' end of MC29 RNA and codes together with other sequences of viral RNA for a MC29-specific, nonstructural protein of 120,000 daltons (9) that is also expressed in transformed cells (4). Therefore, it was suggested that this sequence is a candidate for the onc gene of MC29 (9).…”
Section: Introductionmentioning
confidence: 99%
“…This sequence maps between 2.5 and 4 kb from the 3' end of MC29 RNA and codes together with other sequences of viral RNA for a MC29-specific, nonstructural protein of 120,000 daltons (9) that is also expressed in transformed cells (4). Therefore, it was suggested that this sequence is a candidate for the onc gene of MC29 (9).A definitive identification of the onc genes of MC29 and MH2 is complicated by the defectiveness of these viruses in all three replicative genes of avian tumor viruses (3-5, 10, 11). It is impractical to detect onc deletion mutants, a capability that proved essential for the definition of the src gene of Rous sarcoma virus (RSV) (12-16), because onc deletions of MH2 or MC29 would lack detectable biological markers of any viral gene.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins seem to be fusion proteins between part or all of the gag gene product (specifying viral core proteins) and a unique portion which is similar in viruses with similar biological specificity only (Kitchener & Hayman, in press). This, in addition to the co-linearity of the unique ("transforming") sequences in the RNA of AEV and MC29 with the corresponding fusion proteins (Kitchener & Hayman, in press;Mellon et al, 1978;Lai et al, 1979) suggests that they represent the transforming proteins of DLVs.…”
mentioning
confidence: 99%